Development of Water Recognition Skills Training Model in Intelectual Dissability - Wendri Maryadi; Achmad Sofyan Hanif; Wahyuningtyas Puspitorini (Universitas PGRI Palembang, 2022)
Children who first practice swimming, must first be introduced to the properties of water. The introduction of water really needs to be applied to all those who want to learn swimming specifically for children with intellectual disabilities, of course it is very important to do water swallowing. The achievement of objectives in the training process cannot be separated from the role of the trainer in creating a harmonious training atmosphere in the training environment. The purpose of this study was to develop a water recognition exercise model for mentally retarded children. The development of this research refers to Borg and Gall. The subjects in this study were 42 students. Data collection techniques carried out by observation, study documentation, interviews, and tests. Data analysis was carried out qualitatively and quantitatively. The development of the model through small trials, large trials and effectiveness tests. Test the effectiveness of this water recognition model using the significance test Pre-test and Post-test significance test for differences with SPSS 25 in the results of t-count = -28,971, db = 43 and p-value = 0.00 & lt; 0.05 which means that there are significant differences in the ability of students before and after being given a water recognition skills training model in mentally retarded children. In this study conclusions can be drawn. (1) Model of water recognition skills training exercises for mentally retarded children can be developed and applied in training mentally retarded children (2) Models of water recognition skills training exercises for mentally retarded children can effectively improve the water recognition abilities of mentally retarded children.